Influence of heat input on mechanical and microstructure features of AISI 304 austenitic stainless-steel joints fabricated by TIG spot welding - Aljanabi, Mohammed K.; Mohammed Abdulridha, Marwah; Hassan, Ekhlas; Al-Khafaji, Zainab (UiTM Press, 2026)
The welding experiments were performed with a current range of 45 A to 90 A, a welding time of 3 s to 5 s, and an electrode-to-cup gap of 1.5 mm to 3.0 mm under pure argon shielding gas. Based on process parameters, the heat input domain was associated with nugget diameter, ambient ferrite morphology, tensile shear strength of weld joints, and the nature of fracture and the microhardness distribution in fusion zone (FZ), partially melted zone (PMZ), and heat-affected zone (HAZ). Examinations by optical and scanning electron microscopy showed that all weld zones comprised δ-ferrite in an austenitic matrix, whose morphology evolved from lath to vermicular scales with increasing heat input. Maximum tensile shear strength (4179 N) and weld toughness (5.529 J) were achieved for a balanced δ-ferrite content and an optimal average nugget size of 5.65 mm at 75 A, 3 s, and 1.5 mm, over high heat input of 90 A produced low mechanical features by over penetration and grain coarsening. The microhardness of the welded region increased to about 250 HV at a medium heat input. In contrast, a high heat input resulted in coarsening of δ-ferrite and a decrease in hardness. All fractures initiated in the PMZ, which was determined to be a critical region for joint failure. These results provide a process–structure– property framework to guide the optimization of tungsten inert gas (TIG) spot-welding parameters for thin-gauge stainless steels requiring high joint integrity.